2022
DOI: 10.1159/000524147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Docosahexaenoic Acid Supplementation on Very Preterm Infant Growth: Secondary Outcome of a Randomized Clinical Trial

Abstract: <b><i>Introduction:</i></b> The aim of the study was to determine the effect of a maternal docosahexaenoic acid (DHA) supplementation during lactation, compared with a placebo, on the neonatal growth profile of breastfed very preterm infants. <b><i>Methods:</i></b> Preterm infants’ growth profile, growth velocity from birth to 36 weeks’ postmenstrual age (PMA), and growth at 36 weeks’ PMA were pre-specified secondary outcomes of a randomized placebo-controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…57 ) do show that ~17% of the findings have a significant sex difference and that this is primarily observed in the CBD alone group. This is an important consideration for future studies because the effectiveness of fatty acid supplementation to pre-term infants while breast feeding has been shown to be sex-dependent, with females exhibiting better treatment outcomes [ 45 ], and use of CBD during pregnancy is on the rise Our analysis of sex differences in lipids showed that females in the CBD group tended to have lower levels than males, particularly of in N -acyl alanines, N -acyl leucines, N -acyl valines, 2-acyl glycerols, and, importantly, free fatty acids ( Supplemental Fig. 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…57 ) do show that ~17% of the findings have a significant sex difference and that this is primarily observed in the CBD alone group. This is an important consideration for future studies because the effectiveness of fatty acid supplementation to pre-term infants while breast feeding has been shown to be sex-dependent, with females exhibiting better treatment outcomes [ 45 ], and use of CBD during pregnancy is on the rise Our analysis of sex differences in lipids showed that females in the CBD group tended to have lower levels than males, particularly of in N -acyl alanines, N -acyl leucines, N -acyl valines, 2-acyl glycerols, and, importantly, free fatty acids ( Supplemental Fig. 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Significant genes were then processed using enrichR (version 3.0) (137) along fgsea (version 1.22.0) (138) to find enriched biological pathways present. RNA velocity estimation was done using cellranger output files, then sorted with samtools (1.14), then used velocyto (0.17)(139), then scVelo (0.2.4)(140). Cell-cell communication was analyzed using Cellchat (version 1.4.0) (83) on room air and hyperoxia samples separately with the software’s default parameters.…”
Section: Methodsmentioning
confidence: 99%